Increasing flexibility towards a virtual district heating network. (October 2021) - Schrammel, Harald; Kelz, Joachim; Gruber-Glatzl, Wolfgang; Halmdienst, Christian; Schröttner, Josef; Leusbrock, Ingo
Abstract: The development over the last decade of the district heating (DH) network of Gleisdorf (Austria) represents an innovative example for a transition to a 4th generation DH network (4GDH). The local DH operator has strong ambitions towards implementing a highly efficient, nearly 100% renewable DH system using local resources. These goals will be achieved by the development and implementation of a novel control strategy, namely a "Virtual Heating Plant" (VHP) control concept. The VHP concept is an intelligent high level control system using operating data for real time calculations and a 24h prediction to optimise the overall DH network. The VHP control is fully implemented into the DH system and led to an improved and more flexible unit commitment, higher solar yields and more stable operating conditions. This paves the way to integrate multiple decentralised local heat sources and existing boiler units as well as other systemic approaches (e.g. sector coupling with waste water treatment plant, cascading heat supply out of the return pipe, stepwise system temperature reduction, implementation of an intelligent, decentral storage concept) and non-technical measures (e.g. user and stakeholder integration).